Analisis Pengelolaan Piutang Pada PT Garuda Mandiri Beton Balikpapan - Nurannisa firliana (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2018)
Nurannisa Firliana, 2017, Faculty of Economics and Business at Mulawarman University under the title of Thesis: Analysis of Receivables Management of PT Garuda Mandiri Beton Balikpapan. This research is under the guidance of Mr. H. Hamid Bone as First Counselor and Mrs. Salmah Pattisahusiwa as Second Counselor.          The research took the object of research at PT Garuda Mandiri Beton Balikpapan which since its establishment in 2014 with a focus on issues that will be studied is how the general description of receivables management and receivable turnover rate based on analysis of financial statements of 2014-2016.          This research is qualitative descriptive type by taking the object under study which is the turnover rate of receivable company in a period, the period of receivable collection, the ratio of arrears and the billing ratio. All the ratios collected are the results of further analysis of the financial statements of 2014-2016 which shows a picture of the company's unfavorable conditions. Data collection method used in this research is documentation and field observation.          Based on the results of the analysis obtained from the research, the Company shows unoptimal and effectived management of accounts receivable company. Due to the receivable turnover (RTO), receivables collection period (ACP) and Bills and Delinquent Ratios haven`t yet reached the effectiveness and efficiency standards of each account.          Good turnover and accounts receivable analysis can affect the rate of return of receivables that can increase working capital. Keywords: Receivables Management, Working Capital, Financial Statement, Current Assets